The ocean would paint me blue - Katouh, Zoulfa (London ; India : Bloomsbury ; Thomson Press, 2026)
Following her mother's death, seventeen-year-old Syrian American Jihad Dabbagh is sent to a prestigious New York school, where she navigates new classmates, bullying, and grief as her art helps her find her voice and learn to stand up for what she believes in.
First Published
Ages 12 and up
Keywords: Self-actualization -- Fiction; Art -- Fiction; Bullies and bullying -- Fiction; Schools -- Fiction; Grief -- Fiction; Syrian Americans -- Fiction; Novels; Fiction